Recent progress in quantum dot based sensors - Cui, Lei; He, Xiao-Peng; Chen, Guo-Rong (RSC advances, 2015)
This review summarizes the recent progress in quantum dot (QD) based sensors used for the photoluminescent detection of a variety of species in vitro and in vivo . New trends in using these nanomaterials for sensing applications are highlighted. Recent progress in quantum dot (QD) based chemo- and biosensors for various applications is summarized.